Ali Mazrui - Ebrahim Rasool (International Institute of Islamic Thought, 2016)
On the occasion of the passing of Ali Mazrui, Rashied Omar, imam of the Claremont Main Road Mosque in Cape Town, South Africa, invoked probably the most appropriate verse of the Qur’an to memorialize him: “God bears witness that there is no god but Allah, and so do the angels and those possessed of knowledge, standing firm on justice. There is no God but Allah, the Exalted, the Wise” (Q. 3:18). There are many who testify to belief in the unity of God, and fewer who accept its corollary, the unity of creation and the unity of humanity. There are many who qualify for the description of possessing knowledge by virtue of qualifications obtained in institutions of learning, whether Islamic or other. It is, however, the third angle of this triangle – the triangle of belief, knowledge, and justice – where the world experiences a deficit. Standing for justice is the point of the triangle that is least populated, or if it is populated, it may well be populated in the absence of understanding the implications of belief in the unity of God or understanding the dynamism of knowledge. Mazrui will be remembered for epitomizing the completeness and perfection of this golden triangle, for indeed his knowledge was founded in his unflinching commitment to tawḥīd (unity) and this, in turn, impelled him toward utilizing his intellect both for identifying the sources of injustice in the world and positing theoretical and practical solutions towards justice ...